DNA methylation as a biomarker of salinity and contaminant stress in mangrove crab Ucides occidentalis - Kim Pham; Andrée De Cock; Long Ho; Claudio Peter D'Incal; Wim Vanden Berghe; Dominguez Granda Luis; Filip M.G. Tack; Pieter Spanoghe; Peter L.M. Goethals (Marine Pollution Bulletin, 2026)

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Role of Perindopril in Mitigating Doxorubicin’s Vascular Toxicity in a Rat Model - Anna Marada; Tibor Stračina; Filip Marhefka; Lucie Šůstková; Jaroslav Nádeníček; Jindra Smutná; Peter Scheer; Jana Hložková; Michal Hendrych; Christian Studenik; Hana Paulová; Marie Nováková (Cardiovascular Toxicology, 2026)
Doxorubicin (DOX), a widely used anthracycline in cancer therapy, is associated with significant cardiovascular toxicity. While its cardiotoxic effects are well documented, the mechanisms and prevention of DOX-induced vascular toxicity remain insufficiently explored. Angiotensin-converting enzyme inhibitors (ACEIs), such as perindopril (PER), are commonly used in cardiovascular disease management and may offer vascular protection during chemotherapy. Female ovariectomized Wistar rats were treated with i.v. DOX and/or p.o. PER over five weeks. Cardiac and vascular function were assessed using high-frequency ultrasound and ECG. Vascular reactivity was evaluated in isolated aortal rings using phenylephrine (PE), acetylcholine (ACh), L-N-Nitro arginine methyl ester hydrochloride (L-NAME), and verapamil (VER). Oxidative stress was assessed via plasma 4-hydroxy-2-nonenal (4-HNE) levels, and structural changes were monitored through intima-media thickness (IMT) measurements. DOX administration significantly impaired vascular reactivity, as evidenced by increased contractile responses to PE and reduced endothelium-dependent relaxation. These functional alterations were accompanied by elevated plasma 4-HNE levels, indicating enhanced oxidative stress. Co-treatment with PER preserved vascular responsiveness, reduced contractile tension, and significantly lowered 4-HNE concentrations. Structurally, IMT increased in control and PER-only groups, likely due to post-ovariectomy remodelling, while DOX-treated groups showed no IMT progression. PER co-treatment appeared to stabilize IMT values. PER mitigates DOX-induced vascular toxicity, likely through endothelial protection and reduction of oxidative stress. These findings support the potential use of ACEIs as prophylactic agents in patients undergoing anthracycline-based chemotherapy and highlight the need for further translational studies in cardio-oncology. Graphical Abstract

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Not only aboveground biomass: Soil of undisturbed Carpathian beech forests also stores substantial carbon - Laxmi Moktan; Jeňýk Hofmeister; Filip Oulehle; Otmar Urban; Ion Catalin Petritan; Any Mary Petritan; Michal Bosela; Heather Keith; Peter Jaloviar; Stanislav Kucbel; Ján Pittner; Natálie Pernicová; et al. (Forest Ecology and Management, 2025)

Pathways to an integrated understanding of marine environments and ecosystems in the Asia-Pacific Region - Hanani Adiwira; Sayaka Yasunaka; Jamie M. Kass; Ayşe H. O. Açıkbaş; Sekar Adiningsih; Emma Gairin; Hovaldo B. C. Ilham; Elisa Lahcene; Yanguo Li; Gaku Nishihira; Paula Peñalver-Pereira; Florence M. P. Sie; et al. (Frontiers in Marine Science, 2025)
The Asia-Pacific Region (APR) encompasses a vast geographical area rich in marine biodiversity that plays critical roles in global ecological stability and climate regulation, but it also faces daunting challenges in maintaining these roles under global change. Environmental dynamics in the APR manifest regularly over a range of timescales, including storms, earthquakes, floods, and extreme heat events. Further, coastal and marine ecosystems, including extensive commercial fisheries and coral reefs, are under threat from intense resource extraction and increasingly frequent marine heatwaves. Knowledge gaps for understanding these complex systems are aggravated by substantial barriers to cross-national efforts caused by the region’s vast diversity of cultures, languages, socioeconomics, politics, and management practices. Effective management of marine resources in the APR will necessitate multidisciplinary research based on continuous, region-wide observations supported by robust collaborations. In 2023, we gathered APR researchers across disciplines to discuss these issues and find solutions during a thematic seminar and workshop program at Tohoku University in Japan. Based on the results of this program, we present a review of the current state of APR marine ecosystems, raise key questions addressable through multidisciplinary approaches, and identify future priorities for the region. We conclude that sustaining biodiversity, ecosystem functions, and climate resilience in the APR will depend on stronger interdisciplinary collaboration, better integration of biological and geophysical data, and broader access to marine observations. These efforts are both urgent and essential for supporting better science-based policy decisions to address the escalating effects of global change on marine systems across the region.

Subfossil chironomid assemblage shifts indicate Little Ice Age termination, deforestation, and human impact in a subalpine lake catchment - Martina Jambrović; Ladislav Hamerlík; Katarzyna Szarłowicz; Tomáš Hrdý; Rastislav Milovský; Dubravka Čerba; Filip Jędrzejek; Radovan Pipík; Tímea Chamutiová; Peter Bitušík (Aquatic Sciences, 2025)
Paleoenvironmental reconstruction was conducted on a short sediment core from a subalpine lake (Low Tatra Mountains, Slovakia) spanning the past ~ 300 years, and aimed to assess the impact of climatic oscillations and the well-documented human activities in the catchment. An analysis of subfossil chironomid remains was applied, supported by a land cover reconstruction using historical maps and orthoimagery. Two main phases of lake development were identified: the first, preceding major anthropogenic pressure and the second, which followed the opening of the first hotel in the lake vicinity in 1950, characterised by massive infrastructure and tourism expansion. The oldest assemblages date to the coldest period of the Little Ice Age (LIA) and were dominated by Derotanypus and Paratanytarsus austriacus -type, indicating very cold and oligotrophic conditions. Warming following the end of LIA caused a gradual shift in the taxonomic composition, with previously dominant taxa disappearing or decreasing in abundance. Dominance of Tanytarsus lugens -type, Zavrelimyia and Heterotrissocladius marcidus -type still reflects relatively cold temperatures and low productivity. Taxonomic composition remained mostly stable until the middle of the twentieth century, when construction work in the catchment caused deforestation, the number of year-round tourists increased, and the lake was dammed to improve conditions for boating and angling. The resulting increased nutrient loading, oxygen depletion and macrophyte development are evident from the rising abundances of taxa tolerant of high trophy. The increase of thermally plastic taxa in the twenty-first century reveals recent climate warming, which will likely only exacerbate the already considerable negative human influence, making lake recovery improbable.

Age-related changes in semen characteristics of selected Slovak geese breeds - Eva Tvrdá; Cyril Hrnčár; Filip Benko; Michal Ďuračka; Anton Kováčik; Jakub Vozaf; Andrea Svoradová; Henrieta Arpášová; Miroslava Kačániová; Peter Chrenek (Animal Reproduction Science, 2025)

Content of Biogenic Elements in Sheep Wool by the Regions of Slovakia - Martin Janíček; Martin Massányi; Anton Kováčik; Marko Halo; Filip Tirpák; Martyna Blaszczyk-Altman; Marzena Albrycht; Robert Stawarz; Marko Halo; Peter Massányi (Biological Trace Element Research, 2025)
The quality of nutrition and environmental pollution are crucial chemical indicators influencing animal health, reflected in element concentrations in animal tissues and coats. This study investigates the concentrations of biogenic elements (calcium, potassium, magnesium, sodium, copper, and iron) in sheep wool from various regions of Slovakia to compare concentrations and identify possible correlations between individual elements. Samples were collected from six different regions, and concentrations of elements were measured using flame atomic absorption spectrometry. Statistical analysis revealed significant differences in element levels among the examined regions. Calcium concentrations ranged from 729.2 to 4065 ppm, with the highest concentrations in the Kysuce region and the lowest in the Šariš region. Potassium concentrations ranged from 2315 to 3282 ppm, with the lowest values in the Zemplín region and the highest in the Liptov region. Magnesium, sodium, copper, and iron also exhibited varying concentrations across the regions. Correlation analysis identified significant associations between several elements. The findings suggest that regional environmental differences influence element concentrations in sheep wool, highlighting the importance of monitoring biogenic elements for assessing environmental pollution and animal health. Further research is warranted to explore the underlying mechanisms driving element accumulation in wool and its implications for animal welfare and environmental management.

A call to innovate Antarctic avian influenza surveillance - Michelle Wille; Meagan L. Dewar; Filip Claes; Peter Thielen; Erik A. Karlsson (Trends in Ecology & Evolution, 2025)

Assessment of brain function during stunning and killing of channel catfish (Ictalurus punctatus) - Per Hjelmstedt; Filip To; Peter J. Allen; Albin Gräns (Aquaculture, 2025)

Broomstick experiment with copper in VR-1 reactor - Michal Košťál; Evžen Losa; Tomáš Czakoj; Stanislav Simakov; Marek Zmeškal; Martin Schulc; Jan Šimon; Vojtěch Rypar; Evžen Novák; František Cvachovec; Filip Mravec; Václav Přenosil; et al. (Annals of Nuclear Energy, 2025)

In vitro versus cryo-induced capacitation of bovine spermatozoa, part 3: Compositional and molecular changes to the plasma membrane - Filip Benko; Július Árvay; Ivona Jančo; Michal Ďuračka; Abdollah Mohammadi-Sangcheshmeh; Norbert Lukáč; Peter Ivanič; Eva Tvrdá (Cryobiology, 2024)

Biomarker-based high-throughput sperm phenotyping: Andrology in the age of precision medicine and agriculture - Filip Tirpak; Lauren E. Hamilton; Robert D. Schnabel; Peter Sutovsky (Animal Reproduction Science, 2024)

Use of electroencephalogram (EEG) to optimize stunning efficiency and animal welfare in commercial catfish production - Per Hjelmstedt; Filip To; Albin Gräns; Peter Allen (Aquaculture, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The effect of bee drone brood on the motility and viability of stallion spermatozoa—an in vitro study - Michal Lenický; Ewelina Sidor; Lucia Dianová; Filip Tirpák; Nikola Štefunková; Małgorzata Dżugan; Marko Halo; Marko Halo; Tomáš Slanina; Iveta Urban; Denis Bažány; Agnieszka Greń; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)
Bee drone brood is a beehive by-product with high hormonal activity used in natural medicine to treat male infertility. The aim of the study was to assess the effect of drone brood on stallion spermatozoa during a short-term incubation for its potential use in the equine semen extenders. Three different forms of fixed drone brood (frozen (FR), freeze-dried (FD), and dried extract (DE)) were used. Solutions of drone brood were compared in terms of testosterone, protein, total phenolic content, and antioxidant activity. The stallion semen was diluted with prepared drone brood solutions. The computer-assisted semen analysis (CASA) method was employed to evaluate the movement characteristics of the diluted ejaculate. To determine spermatozoa viability, the mitochondrial toxicity test (MTT) and Alamar Blue test were performed. In terms of testosterone content and antioxidant activity, a close likeness between FR and FD was found whereas DE’s composition differed notably. FR had a positive effect mainly on progressive motility, but also on sperm distance and speed parameters after 2 and 3 h of incubation. On the contrary, FD and DE acted negatively, depending on increasing dose and time. For the first time, a positive dose-dependent effect of fixed drone brood on spermatozoa survival in vitro was demonstrated. Graphical Abstract

Synergistic effect of manganese on zirconia and ceria supports for improving photoreduction of CO2 - Tatiparthi Vikram Sagar; Praveen Kumar; Miroslava Filip Edelmannová; Rudolf Ricka; Martin Reli; Kamila Kočí; Peter Nadrah; Saim Emin; Andrijana Sever Škapin; Urška Lavrenčič Štangar (Journal of Environmental Chemical Engineering, 2024)

A scoring system for histological evaluation of skin during Staphylococcus aureus infections - Peter Makovický; Edita Jeklová; Břetislav Lipový; Filip Raška; Martin Knoz; Rea Jarošová; Šárka Kobzová; Lukáš Vacek; Adam Norek; Lubomír Janda (Biologia, 2023)

Analysis and modelling of single domain core-shell (αFeNi/chromite) nanoparticles emitted during selective laser melting, and their magnetic remanence - Richard Dvorsky; Jana Kukutschová; Marek Pagáč; Ladislav Svoboda; Zuzana Šimonová; Kateřina Peterek Dědková; Jiří Bednář; Rafael Gregorio Mendes; Dalibor Matýsek; Ondřej Malina; Jiří Tuček; Zuzana Vilamová; et al. (Journal of Cleaner Production, 2023)

Health risk-benefit assessment of the commercial red mangrove crab: Implications for a cultural delicacy - Andrée De Cock; Marie Anne Eurie Forio; Siska Croubels; Luis Dominguez-Granda; Liesbeth Jacxsens; Carl Lachat; Heydi Roa-López; Jenny Ruales; Victoria Scheyvaerts; Michelle Carolina Solis Hidalgo; Pieter Spanoghe; Filip M.G. Tack; et al. (Science of The Total Environment, 2023)

The nutritional quality of the red mangrove crab (Ucides occidentalis), harvested at two reserves in the Guayas estuary - Andrée De Cock; Marie Anne Eurie Forio; Bruno De Meulenaer; Filip Tack; Luis Dominguez-Granda; Peter L.M. Goethals (Food Chemistry, 2023)

Calibration of the comet assay using ionising radiation - Gunnar Brunborg; Dag M. Eide; Anne Graupner; Kristine Gutzkow; Sergey Shaposhnikov; Marcin Kruszewski; Nikolai Sirota; George D.D. Jones; Gudrun Koppen; Filip Vanhavere; Peter Møller; Rudolf Stetina; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Macroinvertebrate assemblages in acidified mountain lake inflows differs from lake outflows: the influence of lakes - Kateřina Dočkalová; Takaaki Senoo; Daniel Vondrák; Pavel Chvojka; Jiří Kopáček; Lenka Kamasová; Filip Beneš; Jan Špaček; Jolana Tátosová; Peter Bitušík; Arne Fjellheim; Evžen Stuchlík (Biologia, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Transcription factor c-Myb: novel prognostic factor in osteosarcoma - Kamila Říhová; Monika Dúcka; Iva Staniczková Zambo; Ladislava Vymětalová; Martin Šrámek; Filip Trčka; Jan Verner; Stanislav Drápela; Radek Fedr; Tereza Suchánková; Barbora Pavlatovská; Eva Ondroušková; et al. (Clinical & Experimental Metastasis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Fat causes necrosis and inflammation in parenchymal cells in human steatotic liver - Eddie Wisse; Filip Braet; Gerald J. Shami; Bartlomiej Zapotoczny; Celien Vreuls; Pauline Verhaegh; Peter Frederik; Peters J. Peters; Steven Olde Damink; Ger Koek (Histochemistry and Cell Biology, 2022)
Adapted fixation methods for electron microscopy allowed us to study liver cell fine structure in 217 biopsies of intact human livers over the course of 10 years. The following novel observations and concepts arose: single fat droplets in parenchymal cells can grow to a volume four times larger than the original cell, thereby extremely marginalizing the cytoplasm with all organelles. Necrosis of single parenchymal cells, still containing one huge fat droplet, suggests death by fat in a process of single-cell steatonecrosis. In a later stage of single-cell steatonecrosis, neutrophils and erythrocytes surround the single fat droplet, forming an inflammatory fat follicle indicating the apparent onset of inflammation. Also, fat droplets frequently incorporate masses of filamentous fragments and other material, most probably representing Mallory substance. No other structure or material was found that could possibly represent Mallory bodies. We regularly observe the extrusion of huge fat droplets, traversing the peripheral cytoplasm of parenchymal cells, the Disse space and the endothelium. These fat droplets fill the sinusoid as a sinusoidal lipid embolus. In conclusion, adapted methods of fixation applied to human liver tissue revealed that single, huge fat droplets cause necrosis and inflammation in single parenchymal cells. Fat droplets also collect Mallory substance and give rise to sinusoidal fat emboli. Therefore, degreasing of the liver seems to be an essential therapeutic first step in the self-repairing of non-alcoholic fatty liver disease. This might directly reduce single-cell steatotic necrosis and inflammation as elements in non-alcoholic steatohepatitis progression.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Changes of small mammal communities with the altitude gradient - Jakub Kamenišťák; Ivan Baláž; Filip Tulis; Imrich Jakab; Michal Ševčík; Zuzana Poláčiková; Peter Klimant; Michal Ambros; Leszek Rychlik (Biologia, 2020)

Inhibition of influenza virus activity by the bovine seminal plasma protein PDC-109 - Robert-William Welke; Ivan Haralampiev; Filip Schröter; Beate C. Braun; Andreas Herrmann; Christian Sieben; Peter Müller (European Biophysics Journal, 2019)

Integrating national Red Lists for prioritising conservation actions for European butterflies - Dirk Maes; Rudi Verovnik; Martin Wiemers; Dimitri Brosens; Stoyan Beshkov; Simona Bonelli; Jaroslaw Buszko; Lisette Cantú-Salazar; Louis-Francis Cassar; Sue Collins; Vlad Dincă; Milan Djuric; et al. (Journal of Insect Conservation, 2019)

Multimodal Molecular Imaging Demonstrates Myeloperoxidase Regulation of Matrix Metalloproteinase Activity in Neuroinflammation - Yinian Zhang; Huateng Dong; Daniel P. Seeburg; Gregory R. Wojtkiewicz; Peter Waterman; Benjamin Pulli; Reza Forghani; Muhammad Ali; Yoshiko Iwamoto; Filip K. Swirski; John W. Chen (Molecular Neurobiology, 2019)

Diet of shrews (Soricidae) in urban environment (Nitra, Slovakia) - Kamenišťák Jakub; Klimant Peter; Tulis Filip; Michal Ševčík; Baláž Ivan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Progress in biocatalysis with immobilized viable whole cells: systems development, reaction engineering and applications - Milan Polakovič; Juraj Švitel; Marek Bučko; Jaroslav Filip; Vilém Neděla; Marion B. Ansorge-Schumacher; Peter Gemeiner (Biotechnology Letters, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Lipid dynamics in boar sperm studied by advanced fluorescence imaging techniques - Filip Schröter; Ulrike Jakop; Anke Teichmann; Ivan Haralampiev; Astrid Tannert; Burkhard Wiesner; Peter Müller; Karin Müller (European Biophysics Journal, 2016)

The dynamics of architectural complexity on coral reefs under climate change - Yves‐Marie Bozec; Lorenzo Alvarez‐Filip; Peter J. Mumby (Global Change Biology, 2015)
One striking feature of coral reef ecosystems is the complex benthic architecture which supports diverse and abundant fauna, particularly of reef fish. Reef‐building corals are in decline worldwide, with a corresponding loss of live coral cover resulting in a loss of architectural complexity. Understanding the dynamics of the reef architecture is therefore important to envision the ability of corals to maintain functional habitats in an era of climate change. Here, we develop a mechanistic model of reef topographical complexity for contemporary Caribbean reefs. The model describes the dynamics of corals and other benthic taxa under climate‐driven disturbances (hurricanes and coral bleaching). Corals have a simplified shape with explicit diameter and height, allowing species‐specific calculation of their colony surface and volume. Growth and the mechanical (hurricanes) and biological erosion (parrotfish) of carbonate skeletons are important in driving the pace of extension/reduction in the upper reef surface, the net outcome being quantified by a simple surface roughness index (reef rugosity). The model accurately simulated the decadal changes of coral cover observed in Cozumel (Mexico) between 1984 and 2008, and provided a realistic hindcast of coral colony‐scale (1–10 m) changing rugosity over the same period. We then projected future changes of Caribbean reef rugosity in response to global warming. Under severe and frequent thermal stress, the model predicted a dramatic loss of rugosity over the next two or three decades. Critically, reefs with managed parrotfish populations were able to delay the general loss of architectural complexity, as the benefits of grazing in maintaining living coral outweighed the bioerosion of dead coral skeletons. Overall, this model provides the first explicit projections of reef rugosity in a warming climate, and highlights the need of combining local (protecting and restoring high grazing) to global (mitigation of greenhouse gas emissions) interventions for the persistence of functional reef habitats.

De novo MECP2 duplications in two females with intellectual disability and unfavorable complete skewed X-inactivation - Nathalie Fieremans; Marijke Bauters; Stefanie Belet; Jelle Verbeeck; Anna C. Jansen; Sara Seneca; Filip Roelens; Elfride De Baere; Peter Marynen; Guy Froyen (Human Genetics, 2014)

Alteration of Root Growth by Lettuce, Wheat, and Soybean in Response to Wear Debris from Automotive Brake Pads - Misty D. Dodd; Stephen D. Ebbs; David J. Gibson; Peter Filip (Archives of Environmental Contamination and Toxicology, 2014)

Monocyte heterogeneity in cardiovascular disease - Peter Libby; Matthias Nahrendorf; Filip K. Swirski (Seminars in Immunopathology, 2013)

Analysis of ethanol in fermentation samples by a robust nanocomposite-based microbial biosensor - Jana Šefčovičová; Jaroslav Filip; Vladimír Mastihuba; Peter Gemeiner; Jan Tkac (Biotechnology Letters, 2012)

Integrated Constructed Wetlands (ICW): Ecological Development in Constructed Wetlands for Manure Treatment - Pieter Boets; Evi Michels; Erik Meers; Koen Lock; Filip M. G. Tack; Peter L. M. Goethals (Wetlands, 2011)

Changes in gene expression during male meiosis in Petunia hybrida - Filip Cnudde; Veena Hedatale; Hans de Jong; Elisabeth S. Pierson; Daphne Y. Rainey; Marc Zabeau; Koen Weterings; Tom Gerats; Janny L. Peters (Chromosome Research, 2006)

Results from the Covered Catchment Experiment at Gårdsjön, Sweden, after Ten Years of Clean Precipitation Treatment - Filip Moldan; Richard A. Skeffington; Carl-Magnus Mörth; Peter Torssander; Hans Hultberg; John Munthe (Water, Air, & Soil Pollution, 2004)